Validating Invalidation: Examining the Construct Validity of the Illness Invalidation Inventory Among Individuals With Chronic Low Back Pain. Issue 5 (May 2020) - Molzof, Hylton E.; Newman, Andrea K.; Barnett, Michael D.; Guck, Adam; Scott, Whitney; Sturgeon, John A.; Trost, Zina
Abstract : Objectives: The Illness Invalidation Inventory (3*I) was designed to assess individuals' perceived invalidation regarding chronic pain experiences. However, no study has yet investigated the psychometric properties of the 3*I among individuals with chronic low back pain (CLBP). Given the personal and societal impact of CLBP and the potential for invalidation associated with this condition, the current study sought to examine the psychometric properties of the 3*I among individuals with CLBP. Materials and Methods: Community-dwelling adults with CLBP living in the Southwestern United States ( N =134) completed the 3*I. In line with previous literature, current analyses focused on the 3*I "family members" subscale. Exploratory and confirmatory factor analysis was performed on participant responses. Hierarchical linear regression analyses examined the relationship between the identified factors and participant self-reported pain severity, disability, and depression. Results: Exploratory factor analysis conducted on the 3*I "family members" subscale found 2 factors with high internal consistency (α>0.70) that cumulatively accounted for 49.04% of the variance in scores. Consistent with previous findings, factor loadings suggested that these factors correspond to "discounting" and "lack of understanding." Subsequent confirmatory factor analysis found that this 2-factor model demonstrated a good fit with the data. Greater perceived discounting by family members was associated with greater pain severity, disability, and depression. Discussion: The 2-factor model of the 3*I "family members" subscale identified in the current study reflects previous findings and extends the psychometric validity of the 3*I to a US multiethnic sample of individuals with CLBP.